Synthesis and evaluation of the in vitro and in vivo antitrypanosomal activity of 2-styrylquinolines - Roger Espinosa (Heliyon, 2021)
In this study, we report the synthesis and evaluation of in vitro and in vivo antitrypanosomal activity of styrylquinoline-like compounds (SQ) 3a-h. Synthesis was carried out by using quinaldine and 8- hydroxyquinaldine with a variety of aromatic aldehydes. The structure of SQs was corroborated by one and two-dimension NMR spectroscopy. In vitro antitrypanosomal activity on T. cruzi Talahuen strain was evaluated using β-galactosidase enzymatic method; cytotoxicity on U-937 cells was assessed by using MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] method. On the other hand, in vivo therapeutical response to 3a-f compounds was evaluated in BALB/c mice (Mus musculus) experimentally infected with T. cruzi blood trypomastigotes and then orally administered with 100 mg/kg weight day for 20 days. All of the compounds showed in vitro activity with EC50 values ranging between 4.6 ± 0.1 μg/mL (14.4 μM) and 36.6 ± 6.1 μg/mL (91 μM). Furthermore, treatment with 3a-f compounds for 20 days resulted in improvement in all of the mice, with a 83–96% decrease in parasitic load at day 90 post-treatment. Treatment with benznidazol (BZ) managed to cure 100% of the mice at the end of treatment. None of the treatments affected the weight of the animals or alanine aminotransferase (ALT), blood urea nitrogen (BUN) and creatinine levels in serum. These results suggest a therapeutic potential of 3a-f compounds as treatment for the infection.